CO2 emission reduction potential assessment using renewable energy in India. (15th February 2016) - Kumar, Subhash; Madlener, Reinhard
Abstract: The Indian power sector is experiencing a lot of pressure to supply sustainable electricity at affordable cost due to heavy demand especially in the summer peak season. Most of India's electricity is produced by fossil fueled power plants, which are the source of CO2 emissions. In this case, renewable energy sources play a vital role in securing sustainable energy without environmental emissions. This paper examines the effects of renewable energy use in electricity supply systems and estimates the CO2 emissions by developing various scenarios under the least cost approach. The LEAP energy model is used to develop these scenarios. The results show that in a ARET (accelerated renewable energy technology) scenario, 23% of electricity is generated by renewables only, and 74% of CO2 reduction is possible by 2050. If the maximum energy savings potential is combined with the ARET scenario, the renewables share in electricity supply rises to 36% as compared to the reference scenario, while the CO2 emission reduction in this case remains at 74%. Highlights: The effect of renewable energy use in India's electricity supply system has been examined. CO2 mitigation in different scenarios from a least-cost perspective has been estimated. The LEAP model is used for developing alternative energy supply scenarios. In an accelerated renewables scenario, their share rises to 23% by 2050 (−74% CO2 ). Combining the scenarios with energy efficiency, the renewable share rises to 36% in 2050.